Exercise capacity in athletes with mouthguards - von Arx, T.; Flury, R.; Tschan, J.; Buergin, W.; Geiser, T. (International Journal of Sports Medicine, 2008)
The objective of this study was to determine the effect of wearing a mouthguard on maximal exercise capacity and cardiopulmonary parameters at peak workload, and to assess the athletes' attitudes toward wearing a mouthguard. Thirteen volunteer male athletes (18 to 27 years old) were interviewed before and after delivery of a custom-made laminated mouthguard. A visual analogue scale (VAS, 0 - 100 mm) was used for judgment of interference with breathing, speaking, concentration and athletic performance. In addition, the athletes were subjected to a cardiorespiratory examination on a cycle ergometer with and without mouthguards. Subjectively, the athletes rated the mean interference with performance to be 37 mm VAS at the beginning of the study. Mean scores of impairment decreased to 23 mm VAS (p = 0.081) after wearing the mouthguard for four weeks, and further improved to 12 mm VAS (p < 0.001) after the test on the cycle ergometer. Objectively, the maximum workload during spiroergometry was even slightly elevated during exercise with the mouthguard (330.2 W) compared to exercise without the mouthguard (314.5 W). Peak minute ventilation and oxygen uptake were not different during exercise with and without the mouthguard. The present study demonstrated that a custom-made mouthguard does not significantly affect or reduce maximum exercise performance of athletes.